Implementasi Program Tanggung Jawab Sosial dan Lingkungan (TJSL) Perspektif Maqashid al-Syariah (Studi Pengembangan UMKM Mitra Binaan PT Pupuk Sriwidjaja Palembang) - Muhammad Wahyudi; Muhammad Lathoif Ghozali; Gilang Rizki Aji Putra (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The article entitled "Implementation of the Social and Environmental Responsibility Program (TJSL) Maqashid al-Syariah Perspective (Study of MSME Development Development Partners PT Pupuk Sriwidjaja Palembang)." This study aims to answer questions about how to implement social and environmental responsibility programs at PT Pupuk Sriwidjaja Palembang; how is the sustainability of the social and environmental responsibility program at PT Pupuk Sriwidjaja Palembang; how is the social and environmental responsibility program at PT Fertilizer Sriwidjaja Palembang from the maqashid al-syariah perspective. The method used is a qualitative descriptive approach. Data collection employing interviews and documentation with PT Pupuk Sriwidjaja Palembang with several fostered partner owners to explore the implementation of social and environmental responsibility programs, the sustainability of social and environmental responsibility programs, and how to analyze the maqashid al-syariah perspective, namely protecting assets (al- lazy). The results of this study indicate that providing an overview and information regarding the implementation of social and environmental responsibility programs by PT Pupuk Sriwidjaja Palembang is a form of corporate social responsibility that has fulfilled the triple bottom line dimension. The social extent is carried out through environmental development activities and development partners, the ecological size is implemented through tree planting activities, and the financial dimensions are through providing financing to SME business actors.Keywords: TJSL; MSME; Maqashid al-shariahKeywords: TJSL; MSME; Maqashid al-shariah  AbstrakTulisan yang berjudul “Implementasi Program Tanggung Jawab Sosial dan Lingkungan (TJSL) Perspektif Maqashid al-Syariah (Studi Pengembangan UMKM Mitra Binaan PT Pupuk Sriwidjaja Palembang).” Penelitian ini bertujuan untuk menjawab pertanyaan tentang bagaimana implementasi program tanggung jawab sosial dan lingkungan di PT Pupuk sriwidjaja Palembang; bagaimana sustainability program tanggung jawab sosial dan lingkungan di PT pupuk sriwidjaja Palembang; bagaimana program tanggung jawab sosial dan lingkungan di PT pupuk Sriwidjaja Palembang perspektif maqashid al-syariah. Metode yang digunakan yakni pendekatan deskriptif kualitatif. Pengambilan data dengan cara wawancara dan dokumentasi kepada PT Pupuk Sriwidjaja Palembang dengan beberapa owner mitra binaan untuk menggali tentang implementasi program tanggung jawab sosial dan lingkungan, sustainability program tanggung jawab sosial dan lingkungan, serta bagaimana analisis perspektif maqashid al-syariah yakni perlindungan harta (al-maal). Hasil dari penelitian ini menunjukkan bahwa memberikan gambaran dan informasi mengenai penerapan program tanggung jawab sosial dan lingkungan oleh PT Pupuk Sriwidjaja Palembang merupakan wujud tanggung jawab sosial perusahaan yang sudah memenuhi dimensi triple bottom line, dimensi sosial dilaksanakan melalui kegiatan bina lingkungan dan mitra binaa, dimensi environmental dilaksanakan melalui kegiatan penanaman pohon, dan dimensinsi financial melalui pemberian pembiayaan kepada pelaku usaha UKM.Kata Kunci: TJSL; UMKM; Maqashid al-syariah